ANALYSIS OF FACTORS AFFECTING THE SAVINGS OF PRIVATE PROFIT COMPANIES IN BOSNIA AND HERZEGOVINA EXPRESSED IN RELATIVE AMOUNT OF GDP BY APPLYING THE ARDL METHODOLOGY (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2021)
Purpose: This paper is aimed at analyzing one component of private savings and its factors, namely the savings of private profit companies.Methodology: An analysis was conducted of the savings of the private profit companies in Bosnia and Herzegovina (BiH), which, viewed as the sum of savings and time deposits, recorded a cumulative growth of 78.72% until the outbreak of the global financial crisis. In order to examine what factors favored such positive developments the ARDL methodology was applied.Results: The variables that statistically significantly affect the savings of private profit companies in BiH are GDP growth rate, deposit interest rate, money supply in % of GDP and current account balance in % of GDP (marginally significant at 6% significance level).Conclusion: The methodology applied confirmed the hypothesis of the paper, which proposes that the savings of private profit companies in BiH are significantly influenced by variables of the financial type.